Photocatalytic degradation of naphthalene using calcined FeZnO/ PVA nanofibers. (August 2018) - Sekar, Aiswarya Devi; Muthukumar, Harshiny; Chandrasekaran, Nivedhini Iswarya; Matheswaran, Manickam
Abstract: Recently, the incorporation of metal oxide nanoparticles into polymers has gained great attention owing to their ample of applications. The green mediated synthesis Fe-doped ZnO nanoparticles have been incorporated into PVA nanofibers through electro spinning for the application of photocatalytic degradation. The PVA polymer concentration was optimized to obtain uniform fibers without beads. The Fe-doped ZnO nanofibers were characterized by various analyzing techniques. The results show that good physicochemical with high surface area, uniformity in fiber with an average diameter ranges from 150 to 300 and 50–200 nm for un-calcined and calcined Fe-doped ZnO nanofiber respectively. The photocatalytic activity of nanofibers was examined by the degradation of naphthalene. The efficiency was observed 96 and 81% for calcined and un-calcined nanofibers, respectively. The reusable efficacy of Fe-doped ZnO calcined nanofiber as a catalyst was studied. These studies corroborated that the calcined Fe-doped ZnO nanofiber as promising material for catalytic applications. Graphical abstract: Synopsis: Facile fabrication of FeZnO/PVA nanofibers for photocatalytic degradation of naphthalene. Image 1 Highlights: Synthesis of Fe-doped ZnO/PVA nanofibers with good physicochemical properties. Optimization and calcination of nanofibers to enhance the degradation capacity. Calcined nanofiber has showed better photocatalytic degradation activity than Un-calcined Fe-doped ZnO/PVA nanofiber. Reusability study has delineated the stability of Fe-doped ZnO nanofiber.